Distinct Trauma Types in Military Service Members Seeking Treatment for Posttraumatic Stress Disorder - Litz, Brett T.; Contractor, Ateka A.; Rhodes, Charla; Dondanville, Katherine A.; Jordan, Alexander H.; Resick, Patricia A.; Foa, Edna B.; Young‐McCaughan, Stacey; Mintz, Jim; Yarvis, Jeffrey S.; Peterson, Alan L. (Journal of traumatic stress, 2018)
We examined the frequency of trauma types reported in a cohort of service members seeking treatment for posttraumatic stress disorder (PTSD) and compared symptom profiles between types. In this observational study, 999 service members (9.2% women; Mage = 32.91 years; 55.6% White) were evaluated using a standardized assessment procedure to determine eligibility for clinical trials. Participants were evaluated for DSM‐IV‐TR‐defined PTSD using the PTSD Symptom Scale–Interview; all participants reported a Criterion A event. Independent evaluators rated descriptions of Criterion A events as belonging to trauma types at a high degree of reliability, κ = 0.80. Aggregated non‐life‐threat primary trauma types were more frequently endorsed than aggregated life‐threat types, 95% CI [17.10%, 29.20%]. Participants who endorsed moral injury–self traumas had a higher level of reexperiencing (d = 0.39), guilt (hindsight bias, d = 1.06; wrongdoing, d = 0.93), and self‐blame (d = 0.58) symptoms, relative to those who reported life threat–self. Participants who experienced traumatic loss had greater reexperiencing (d = 0.39), avoidance (d = 0.22), guilt (responsibility, d = 0.39), and greater peri‐ and posttraumatic sadness (d = 0.84 and d = 0.70, respectively) symptoms, relative to those who endorsed life threat–self. Relative to life threat–self, moral injury–others was associated with greater peri‐ (d = 0.36) and posttraumatic (d = 0.33) betrayal/humiliation symptoms, and endorsement of aftermath of violence was associated with greater peri‐ (d = 0.84) and posttraumatic sadness (d = 0.57) symptoms. War zone traumas were heterogeneous, and non‐life‐threat traumas were associated with distinct symptoms and problems. Resumen Spanish s by the Asociación Chilena de Estrés Traumático (ACET) TIPOS DIFERENTES DE TRAUMA EN MIEMBROS DEL SERVICIO MILITAR QUE BUSCAN TRATAMIENTO POR TRASTORNO DE ESTRÉS POSTRAUMÁTICO TIPOS DE TRAUMA EN MIEMBROS DEL SERVICIO QUE BUSCAN TRATAMIENTO Examinamos la frecuencia de tipos de trauma reportados en una cohorte de miembros del servicio que buscaban tratamiento por trastorno de estrés Postraumático (TEPT), y comparamos el perfil de síntomas entre los tipos de trauma. En este estudio observacional, 999 miembros del servicio (9.2% mujeres; Media de edad = 32,91 años; 55,6% blancos) fueron evaluados usando un procedimiento de evaluación estandarizado para determinar la elegibilidad para los estudios clínicos. Los participantes fueron evaluados según criterios DSM‐IV‐TR para TEPT usando la Entrevista de Escala de Síntomas para TEPT; todos los participantes reportaron un evento del Criterio A. Evaluadores independientes clasificaron la descripción de los eventos del Criterio A como pertenecientes a los tipos de trauma con un alto grado de fiabilidad (ĸ = 0.80). Los tipos de trauma primarios agregados sin amenaza vital fueron endosados con mayor  frecuencia que los tipos agregados con amenaza vital, IC 95% [17.10%, 29,20%]. Los participantes que endosaron traumas por daño moral auto‐infringido tuvieron mayores síntomas de re‐experimentación  (d = 0,39), sentimientos de  culpa  (sesgo retrospectivo, d = 1,06; hacerlo mal, d = 0,93), y autoinculpación (d = 0,58) en relación con aquellos que  reportaron amenaza vital personal. Los participantes que experimentaron pérdidas traumáticas tuvieron mayores síntomas de re‐experimentación (d = 0,39), evitación (d = 0,22), sentimientos de culpa (responsabilidad, d = 0,39) y mayor tristeza peri y postraumática (d = 0,84 y 0,70 respectivamente), en relación con aquellos que reportaron amenaza vital personal. En relación con amenaza vital, de daño moral a otros estuvo más asociado con mayores niveles de síntomas de traición/ humillación peri (d = 0,36) y postraumáticos (d = 0,33), y el endosamiento de las consecuencias de la violencia estuvo asociado con más síntomas de tristeza peri (d = 0,84) y postraumática (d = 0,57). Los traumas de guerra fueron heterogéneos y los traumas sin amenaza de vida estuvieron asociados con problemas y síntomas distintivos. 抽象 Traditional and Simplified Chinese s by AsianSTSS Distinct Trauma Types in Military Service Members Seeking Treatment for Posttraumatic Stress Disorder Traditional Chinese 標題: 尋求治療創傷後壓力症的軍隊成員不同的創傷類型 撮要: 我們透過尋求治療創傷後壓力症(PTSD)的軍隊成員, 檢視創傷類型的頻率, 並比較不同創傷類型的症狀剖象。這項觀察研究的樣本為999名軍隊成員(9.2% 女性; Mage = 32.91 歲; 55.6% 白人)。我們採用標準化評估步驟, 找出樣本是否合適接受臨床試驗, 然後以「PTSD症狀量表會談版」評估樣本是否患有DSM‐IV‐TR介定的 PTSD。所有樣本都曾經歷標準A (Criterion A)事件。獨立的評估員把標準A事件歸類為有高水平倚賴性的創傷類型(κ = 0.80)。相比起整體生命威脅的創傷類型, 較多樣本有整體非生命威脅的主要創傷類型, 95% CI [17.10%, 29.20%]。與有「生命威脅—個人」創傷類型的樣本相比, 有「道德創傷—個人」創傷類型的樣本, 有較高水平的再體驗(d = 0.39)、內疚 (事後聰明偏向, d = 1.06; 犯錯, d = 0.93)、和自責(d = 0.58)症狀。與有「生命威脅—個人」的樣本相比, 曾經歷創傷性損失的樣本有較高水平的再體驗(d = 0.39)、迴避(d = 0.22) 、內疚(責任, d = 0.39), 亦有較大程度的創傷當下和創傷後悲傷 (分別為d = 0.84 和d = 0.70)。與有「生命威脅—個人」的樣本相比, 有「道德創傷—他人」的創傷類型跟創傷當下(d = 0.36)和創傷後(d = 0.33)的背叛༏受辱症狀水平較高有關;受暴力影響跟有較高水平的創傷當下(d = 0.84)和創傷後(d = 0.57)悲傷有關。戰爭創傷具異質性;非生命威脅的創傷跟不同的症狀問題有關。 Simplified Chinese 标题: 寻求治疗创伤后压力症的军队成员不同的创伤类型 撮要: 我们透过寻求治疗创伤后压力症(PTSD)的军队成员, 检视创伤类型的频率, 并比较不同创伤类型的症状剖象。这项观察研究的样本为999名军队成员(9.2% 女性; Mage = 32.91 岁; 55.6% 白人)。我们采用标准化评估步骤, 找出样本是否合适接受临床试验, 然后以「PTSD症状量表会谈版」评估样本是否患有DSM‐IV‐TR介定的 PTSD。所有样本都曾经历标准A (Criterion A)事件。独立的评估员把标准A事件归类为有高水平倚赖性的创伤类型(κ = 0.80)。相比起整体生命威胁的创伤类型, 较多样本有整体非生命威胁的主要创伤类型, 95% CI [17.10%, 29.20%]。与有「生命威胁—个人」创伤类型的样本相比, 有「道德创伤—个人」创伤类型的样本, 有较高水平的再体验(d = 0.39)、内疚 (事后聪明偏向, d = 1.06; 犯错, d = 0.93)、和自责(d = 0.58)症状。与有「生命威胁—个人」的样本相比, 曾经历创伤性损失的样本有较高水平的再体验(d = 0.39)、回避(d = 0.22) 、内疚(责任, d = 0.39), 亦有较大程度的创伤当下和创伤后悲伤 (分别为d = 0.84 和d = 0.70)。与有「生命威胁—个人」的样本相比, 有「道德创伤—他人」的创伤类型跟创伤当下(d = 0.36)和创伤后(d = 0.33)的背叛༏受辱症状水平较高有关;受暴力影响跟有较高水平的创伤当下(d = 0.84)和创伤后(d = 0.57)悲伤有关。战争创伤具异质性;非生命威胁的创伤跟不同的症状问题有关。